Analgesia epidural com morfina ou buprenorfina em pôneis submetidos à sinovite carpal com lipopolissacarídeo - Freitas, Gabrielle Coelho (2009)
Pain control of synovitis is important in the reduction of stress responses, suffering and occurrence of laminitis on the contralateral limb. The use of epidural opioids stands out for its analgesic quality, reduction of doses of the drugs used, reduction of their side effects and prolonged period of action. The study aimed to evaluate the physiological and the analgesic effects of epidural administration of 0.1 mg/kg of morphine or 5 μg/kg of buprenorphine in ponies submitted to synovitis induced with E. coli lipopolysacharide (LPS) in the radiocarpal articulation. Six healthy ponies weighing 131.3 kg and age between 3.5 to 9 years were used and divided randomly in 3 groups and arranged in a Latin Square. The control group (GC) received 0.15 mL/kg of 0.9% NaCl solution, morphine group (GM) received 0.1 mg/kg of morphine and buprenorphine group (GB) 5 μg/kg of buprenorphine via epidural and dilluted in 0.9% NaCl solution, using a stardard total volume of 0.15 mL/kg and time of administration of 10 seconds/mL. After general and specific clinical examination, they were sedated and the carpal synovitis was induced with 0.5 ng of LPS administered to the radiocarpal articulation. Subsequently, an epidural catheter was introduced in the epidural space, so that the treatments would be placed in the thoracolumbar region. 6 hours after LPS, the animals were submitted to a new general and specific clinical exam (time 0) and assigned to one of the treatments. The general physical examination (HR, RR, SAP, CRT, color of mucous membranes, TºC and intestinal motility) and specific (pain on palpation, maximum angle of carpal flexion, pain on maximum flexion, grade of articulation movement, stride lenght and lameness degree) were carried out 30 minutes and 1, 2, 4, 6, 8, 10, 12, 16, 20 and 24 hours after epidural administration of the assigned treatment by a blind examinator. Parametric variables were analyzed with ANOVA, followed by Dunnett test for intra group and Tukey test between groups. For the non-parametric variable Wilcoxon test was used. Differences was considered significant when P<0.05. The synovitis induction model produced changes in the lameness degree, pain on palpation and angle of flexion, maintaining present pain on maximum flexion and reduced grade of articulation movement, but it did not cause changes in the physiological parameters. The control group showed changes in lameness in relation to physiological parameters up to 12 hours. Lameness degree was reduced in GM and GB for 30 minutes up to 12 hours and 6 up to 12 hours, respectively. Regarding physiological parameters, alterations were observed in the intestinal motility, where hypomotility occurred at 1 hour in GM and for 30 minutes up to 1 hour in GB; and body temperature, which was maintained higher in GM and GB up to 10 hours. The intra-articular synovitis induction model with the use of LPS was efficient for 12 hours. Morphine provided analgesia starting at 30 minutes and lasting for 12 hours after its administration, whereas buprenorphine was effective only after 6 hours, lasting for another 6 hours.